Comparison of iron carboxy maltose and iron sucrose in pregnant females - Sunil, Isha; Kour, Prabhjit; Sharma, Mitali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Maternal anaemia is a common problem worldwide. The aim of this study is to compare the efficacy and safety of FCM vs iron sucrose for correction of iron deficiency during pregnancy. Methods: This study was conducted in Swasthya healthcare, Jammu for a period of ten months from Sep 2017 to June 2018. A total of 100 women with Hb 7-9.9g% enrolled. They were divided into two groups of 50 each. Group A were given Iron Carboxy maltose and Group B were given Iron Sucrose. These were compared for their efficacy and safety. Results: In the present study, the rise in mean hemoglobin at 4 weeks in Group A was 1.79±0.47 and 1.06±0.11 in Group B which was highly significant (p-value<0.0001). Rise in mean serum ferritin level at 4 weeks in Group A was 123.80±16.03 and in Group B was 84.78±10.53. Statistically, this rise was also highly significant (p<0.0001). In present study, adverse reactions were observed in 34% patients in Group A, while in Group B it was observed in 52% patients. Conclusions: Iron carboxy maltose shows higher rise in hemoglobin and ferritin levels as compared to Iron Sucrose and incidence of adverse effects is also comparatively lower in the former.